Preventing Pressure Injuries in Neonates Undergoing Therapeutic Hypothermia for Hypoxic-Ischemic Encephalopathy: An Interprofessional Quality Improvement Project. (August 2017) - Luton, Alexandra; Hernandez, Jae; Patterson, Clive "Robert"; Nielsen-Farrell, Jill; Thompson, Anita; Kaiser, Jeffrey R.
Abstract : Background: Hospital-acquired pressure injuries (HAPIs) can be caused by multiple factors including pressure, shear, friction, moisture/incontinence, device-related pressure, immobility, inactivity, and nutritional deficits. Along with immobility, medical device-related (MDR) HAPIs are a primary cause of pressure injury in neonates, as the clinical practice setting has become increasingly technologically advanced. It is estimated that up to 50% of HAPIs are MDR in pediatric patients. Neonates are at particular risk for HAPI because of their specific anatomical, physiological, and developmental vulnerabilities. A specific example of confluent factors that may increase risk for HAPI is the application of therapeutic hypothermia (TH) and continuous electroencephalography monitoring for neonates with hypoxic-ischemic encephalopathy (HIE). Interventions: An interprofessional team collaborated to expand upon existing evidence-based standards of care to address the needs of this specific population within the neonatal intensive care unit (NICU). Interventions centered on revision of current protocols, with efforts to optimize product selection, hardwire assessment practices, and refine documentation of patient care and outcomes. Methods: The team primarily utilized plan-do-study-act (PDSA) cycles to test and refine specific methods and strategies to reduce HAPIs. Tested solutions were adopted, adapted, or abandoned. Results: A sustained zero HAPI rate in the HIE population resulted. The team continues to collect, report, and utilize near-miss data to continue to refine the process as new risks are identified. Implications for Practice: Recognizing the unique skin protection needs of special populations within the NICU, such as those undergoing TH, is crucial. When evidence-based standards of care fail to adequately meet such needs, a collaborative approach to identifying, testing, and implementing population-specific solutions is essential. Implications for Research: A paucity of literature regarding the unique skin protection needs for babies undergoing TH exists. Work should be done to better describe the influence of TH on skin integrity, with the goal of identifying population-specific protective measures.